Neck and upper extremity pain in sonographers – Associations with occupational factors. (January 2017) - Gremark Simonsen, Jenny; Axmon, Anna; Nordander, Catarina; Arvidsson, Inger
Abstract: Sonographers have a high risk of musculoskeletal disorders. This study explores the associations between working conditions and musculoskeletal pain based on the frequency and intensity of pain in the neck and upper extremities. A questionnaire was answered by 291 female sonographers. High prevalence of neck/shoulder pain was associated with eye complaints and headache related to work on the computer, dissatisfaction with the computer workstation, high mechanical exposure index (MEI) and high demands. The possibility to adjust the keyboard and chair, and adequately corrected eyesight were positive factors. High prevalence of elbow/hand pain was associated with performing echocardiography, computer-related eye complaints, high MEI and high job and sensory demands. In echocardiography, working with a straight wrist and holding the transducer with a two-handed grip or alternating hands was associated with a low prevalence of elbow/hand pain. Thus, further improvements in the working conditions are possible and are recommended. Highlights: Sonographers still show a high prevalence of pain and efforts to improve their working environment must continue. Visual conditions should be optimized, including adequate eye sight correction. All components of the equipment should be adjustable. Other ways of handling the transducer in echocardiography should be encouraged.